The Effect of Using Types of Discovery Method in Learning Some Basic Football Skills for Students of the Faculty of Physical Education - Abed Al-Delfi, Kadhim Mhmood; Hasan, Riyadh jumaa (Pubmedia Jurnal Pendidikan Olahraga, 2025)
Developing modern methods for teaching football skills that focus on learner activity and positivity helps develop these skills and accelerate the learning process, particularly by giving the learner a prominent role and enhancing student participation. Accordingly, the main objectives of the research are as follows: The effect of using different types of discovery methods (directed, semi-directed, and free) on learning some basic football skills for first-year students at the College of Physical Education, Al-Qadisiyah University. Identifying which methods are best for teaching some basic football skills for first-year students at the College of Physical Education, Al-Qadisiyah University. To achieve the research objectives, the researchers used the experimental approach using the equivalent groups method, while the research community represented the first-year students in the College of Physical Education / University of Al-Qadisiyah, numbering (100). The research sample was chosen by simple random method, numbering (21) and they were divided into three groups: Section (C) works with the directed discovery method, Section (D) with the semi-directed discovery method, and Section (E) works with the free discovery method. After that, the tests were prepared and the pre-test was conducted for the research sample members. Then the three methods were applied to the research groups, and then the researchers proceeded to apply the post-test. By using appropriate statistical methods to process the results to serve the research and achieve the objectives, the researchers concluded that the free discovery method is the best method for learning the skills of handling, rolling and extinguishing, followed by the semi-directed method, then the directed method, while the directed discovery method was the best method for learning the skills of scoring, followed by the semi-directed method, then the free discovery method.